Impact of obesity on COVID-19 patients - Yu, Wanqi (J Diabetes Complications, 2021)
With the increasing prevalence of obesity, there is a growing awareness of its impact on infectious diseases. In past epidemics of influenza A and Middle East respiratory syndrome (MERS) coronavirus, obesity has been identified as a risk factor influencing the severity of illness in infected persons. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for a large number of deaths and health damages worldwide. Increasing numbers of reports have linked obesity to more severe COVID-19 disease and death. This review focuses on the impact of obesity on patients with COVID-19. We comprehensively analyzed the various mechanisms of obesity affecting the severity of the disease. In addition, on the basis of the vulnerability of people with obesity during the COVID-19 epidemic, we summarized both individual-level and hospital-level prevention and management measures for COVID-19 patients with obesity and discussed the impact of isolation on people with obesity.